الكناية في الحديث والأثر عن فضل العلم في كتاب آداب العالم والمتعلم: دراسة بلاغية: Metonymy in Hadith and Athar on Knowledge’s Virtue in Adab Al-Alim Wal-Mutaallim: A Rhetorical Study - Nisa Halimatussa'adah; Mohamad Anang Firdaus; M. Rizki Syahrul Ramadhan (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
This research issnvestigates the application of al-Kinayah (implicit/metaphorical expression) in the Hadiths and Athars within "The Chapter on the Virtue of Knowledge, Scholars, and the Virtue of Teaching and Learning It" (Bāb Faḍl al-‘Ilm wa al-‘Ulamā’ wa Faḍl Ta‘līmihi wa Ta‘allumihi) from the book "Adab al-'Alim wa al-Muta'allim" written by Hadratus Syaikh Hasyim Asy'ari. The aims of this study are to identify the types of Kinayah, their textual meanings from rhetorical and pedagogical perspectives, and their linguistic purposes within this comprehensive chapter. This study applied a qualitative library research method, focusing on the Kinayah theory within Ilm al-Bayan by analyzing specific selected texts consisting of one Hadith and four Athars. The research findings indicate that: (1) there are various types of Kinayah employed in this specific chapter, predominantly Kinayah 'an al-Sifah (expression of a trait) and Kinayah 'an al-Mawshuf; for instance, the phrase "did not smell the scent of heaven" serves as a Kinayah 'an al-Sifah, illustrating how far a person is from heaven due to insincere intentions in seeking knowledge, (2) the use of Kinayah functions significantly for emphasis (mubalaghah), spiritual warning (zajr), and embodying abstract meanings into sensible images, (3) it reveals deep educational values concerning the integrity of intention, intellectual humility, and the importance of lifelong learning and teaching. This study concludes that Kinayah serves as a powerful educational instrument to instill spiritual values regarding the virtues of acquiring and disseminating knowledge.